THERAPY LOW BACK PAIN WITH SWEDISH MASSAGE, ACUPRESSURE AND TURMERIC - Putri, Dyah Ayu Rhomandhoni; Imandiri, Ario; Rakhmawati, Rakhmawati (Journal of Vocational Health Studies, 2020)
Background: Low back pain is pain that arises below the costal margin and above the inferior gluteal fold. In Traditional Chinese Medicine (TCM) low back pain is referred to as Yao Tong. Low back pain cases experienced by patients are pain that gets worse when exposed to cold air, is too tired and feels stiff and heavy. The patient has low back pain with damp cold pathogenic syndrome. Purpose: To prove the effect of combination therapy for Swedish massage in the back and waist area, acupressure at Shenshu (BL23), Dachangshu (BL25), Taixi (KI3), Taibai (SP3), Fenglong (ST40) and turmeric herbs (Curcuma longa Linn) on low back pain sufferers. Method: Management of low back pain with Swedish, acupressure and herbal massage methods. Swedish massage therapy is performed on the back and waist area. Acupressure at the points of Shenshu (BL23), Dachangshu (BL25), Taixi (KI3), Taibai (SP3), Fenglong (ST40) with the principle of therapy of kidney and spleen tonification and elimination of cold moist pathogens. The most common herbal therapy for patients is turmeric (Curcuma longa Linn). Result: The curcumin compounds in turmeric can inhibit lipoxygenase, phospholipase A2 and COX-2 so they can reduce low back pain. In the treatment of low back pain, massage and acupressure are performed 2 times a week 12 times. While herbal therapy is given for 42 days taken once a day with a dose of 9 grams of turmeric simplicia. Conlussion: Swedish massage therapy, acupressure and herbs can reduce low back pain.